Digital Readiness of Pre-Service Chemistry Teachers for Integrating Technology in STEM Education - Anggiyani Ratnaningtyas Eka Nugraheni; Erfan Priyambodo (PAEDAGOGIA, 2026)
Although the integration of digital technology in STEM education is growing, empirical evidence on the extent to which pre-service chemistry teachers are digitally prepared in terms of technology, pedagogy, and infrastructure is still limited. This study examines the digital readiness of pre-service chemistry teachers to integrate technology into STEM learning across six dimensions: Technology Acceptance, Technology Competence, Technology Control, Pedagogical Readiness, Infrastructure Readiness, and Utilisation of Digital Learning Resources. An embedded mixed-methods approach was employed in this study, integrating quantitative and qualitative methods to explore pre-service chemistry teachers’ digital readiness. Data were collected from 147 pre-service chemistry teachers at a single public University in Yogyakarta, Indonesia, through a validated questionnaire. Quantitative data were analyzed using descriptive statistics. Meanwhile, the qualitative data from open-ended responses were analyzed thematically. The results show that the Technology Acceptance dimension falls into the very good category, reflecting high enthusiasm for adopting digital devices. Conversely, the dimensions of Technological Competence, Technological Control, Pedagogical Readiness, Infrastructure Readiness, and Utilisation of Digital Learning Resources were in the good category, indicating that although pre-service teachers are open to technology, their technical and pedagogical capacities are not yet fully optimal. Furthermore, Augmented Reality, PhET simulations, and Virtual Reality are the most widely used technologies, with limited facilities and a lack of training as the main obstacles. These findings emphasize the importance of structured training, infrastructure improvements, and policy support to strengthen digital pedagogical readiness in STEM education.